An internal model frame-based disturbance attenuation control scheme for quad-rotors transporting unknown payloads. (October 2019) - Li, Hongda; Wang, Yuan; Shi, Zhiwei; Chang, Min
The path following control of quad-rotors transporting uncertain payloads, whose control system is featured with time-variation, high nonlinearity and strong couplings among state variables and inputs, is investigated. Targeting this, an internal model frame-based disturbance attenuation control scheme that requires only rough model information is proposed. Firstly, a novel disturbance estimator (DE) for general single-input-single-output (SISO) system is proposed. Secondly, the DE proposed is applied in transporting unknown payloads by quad-rotors, to estimate the disturbances caused by the payloads for feedback compensation. Lastly, the control scheme based on internal model frame is designed to further reduce the remaining disturbances from disturbance estimation error.